The Predatory Ecology of Deinonychus and the Origin of Flapping in Birds - Fowler, Denver W. (Public Library of Science, 2011)
Most non-avian theropod dinosaurs are characterized by fearsome serrated teeth and sharp recurved claws. Interpretation of theropod predatory ecology is typically based on functional morphological analysis of these and other physical features. The notorious hypertrophied ‘killing claw’ on pedal digit (D) II of the maniraptoran theropod Deinonychus (Paraves: Dromaeosauridae) is hypothesized to have been a predatory adaptation for slashing or climbing, leading to the suggestion that Deinonychus and other dromaeosaurids were cursorial predators specialized for actively attacking and killing prey several times larger than themselves. However, this hypothesis is problematic as extant animals that possess similarly hypertrophied claws do not use them to slash or climb up prey. Here we offer an alternative interpretation: that the hypertrophied D-II claw of dromaeosaurids was functionally analogous to the enlarged talon also found on D-II of extant Accipitridae (hawks and eagles; one family of the birds commonly known as “raptors”). Here, the talon is used to maintain grip on prey of subequal body size to the predator, while the victim is pinned down by the body weight of the raptor and dismembered by the beak. The foot of Deinonychus exhibits morphology consistent with a grasping function, supportive of the prey immobilisation behavior model. Opposite morphological trends within Deinonychosauria (Dromaeosauridae + Troodontidae) are indicative of ecological separation. Placed in context of avian evolution, the grasping foot of Deinonychus and other terrestrial predatory paravians is hypothesized to have been an exaptation for the grasping foot of arboreal perching birds. Here we also describe “stability flapping”, a novel behaviour executed for positioning and stability during the initial stages of prey immobilisation, which may have been pivotal to the evolution of the flapping stroke. These findings overhaul our perception of predatory dinosaurs and highlight the role of exaptation in the evolution of novel structures and behaviours.